Multimodality in Higher Education - Lucía Belles-Calvera (Universitat Jaume I. Department of English Studies, 2018)
Reviewed by Lucía Bellés-Calvera IULMA / Universitat Jaume I, Spain   Multimodality in Higher Education, by Archer and Breuer (2016) deals with multimodal writing practices and pedagogies in tertiary education. With the boost of new technologies in the field of education, studies on modes of communication (e.g. writing) have focused on their evolution throughout the years, particularly in the learning process. This book is aimed at educators and researchers who are interested in the writing communication practices required in a variety of domains, namely architecture, engineering or cultural studies among others. It is true that Multimodality has become quite complex in the past few years given that writing is regarded as a means of knowledge even in practical fields, such as science and media production. In this sense, this volume could be used as a resource book for those educators who want to reflect on the relevance of multimodal competencies when conveying a message, especially when they want to suit students' needs in the near future. At the same time, the content of the book is precise and easy to follow as it includes interviews and pictures that can help readers understand the changes that have taken place in the communication landscape.